Community as contact zone: the power dynamics of community formation on a British council estate. (20th March 2020) - Leaney, Sarah
Abstract: This paper explores the formation of 'community' on a British council estate as a process of negotiation enacted within a 'contact zone', a social space defined by a struggle between different cultural values within asymmetrical relations of power. Building on a discursive turn within theorizations of class, the paper explores the mobilization of discourses of community as a process of making class on The Estate. Based on ethnographic research, the paper offers an analysis of the field dynamics of the Community Centre, where community is enacted, negotiated, subverted and critiqued. This paper shows how a focus on the dynamic nature of discursive reproduction enacted in everyday negotiations within the 'contact zone' moves our understanding beyond structural accounts of class, incorporating agentic responses and everyday resistances into an analysis of the formation of class and community on The Estate.